2016
DOI: 10.1105/tpc.16.00474
|View full text |Cite
|
Sign up to set email alerts
|

DNA DAMAGE BINDING PROTEIN2 Shapes the DNA Methylation Landscape

Abstract: In eukaryotes, DNA repair pathways help to maintain genome integrity and epigenomic patterns. However, the factors at the nexus of DNA repair and chromatin modification/remodeling remain poorly characterized. Here, we uncover a previously unrecognized interplay between the DNA repair factor DNA DAMAGE BINDING PROTEIN2 (DDB2) and the DNA methylation machinery in Loss-of-function mutation in DDB2 leads to genome-wide DNA methylation alterations. Genetic and biochemical evidence indicate that at many repeat loci,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 56 publications
(82 reference statements)
3
41
0
Order By: Relevance
“…5A). By contrast, a FLAG-tagged, DNA-bindingdeficient point-mutant allele of DDB2 (DDB2 K314E -FLAG) (30,31), which failed to rescue the ddb2-3 UV hypersensitivity (Fig. S5A), coimmunoprecipitated with AGO1 significantly less than the WT DDB2-FLAG allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). By contrast, a FLAG-tagged, DNA-bindingdeficient point-mutant allele of DDB2 (DDB2 K314E -FLAG) (30,31), which failed to rescue the ddb2-3 UV hypersensitivity (Fig. S5A), coimmunoprecipitated with AGO1 significantly less than the WT DDB2-FLAG allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA of Arabidopsis DDB2 and DDB2 K314E were amplified by PCR using primers described in ref. 31. Both cDNA were sequenced and cloned into the pOEX2 vector, between the NcoI and AvrII sites (25).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that INVOLVED IN DE NOVO2 (IDN2), a dsRNA binding protein (Ausin et al, 2009;Zheng et al, 2010;Schalk et al, 2016), forms a complex with IDN2 paralog 1 (IDP1) and IDP2 that functions at the effector stage of RdDM (Ausin et al, 2012;Xie et al, 2012;Zhang et al, 2012). In this study, we found that IDN2 was involved in HR repair and that its dsRNA binding activity was required for its function in HR repair.…”
Section: Introductionmentioning
confidence: 79%
“…These findings suggest that the RdDM pathway shares components with diRNA-mediated DSB repair. A recent study has also provided a link between the nucleotide excision repair machinery and the RdDM pathway (Schalk et al, 2016). DNA DAMAGE BINDING2, a protein that is involved in nucleotide excision repair, influences de novo DNA methylation through interacting with AGO4 and controlling the local abundance of hc-siRNAs (Schalk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this also occurs in plant cells is not known. A role for the DDB2 DNA damage factor in DNA methylation through both RdDM and regulation of DNA methylcytosine glycosylase has been shown in Arabidopsis (Schalk et al, 2016). Also, interconnections between sRNAs and DNA damage repair have been reported (Schalk et al, 2017;Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 97%